Induced Unbalance as a Method for Improving the Dynamic Stability of High-Speed Turbochargers - R. Gordon Kirk; Ali A. Alsaeed (International Journal of Rotating Machinery)
The high-speed diesel engine turbocharger is known to have subsynchronous vibrations for a wide speed range. The bearing fluid-film instability is the main source of the vibration. The nonlinear forces inside the bearings are causing the rotor to whirl in a limit cycle. This study presents a new method for improving the dynamic stability by inducing the turbocharger rotor unbalance in order to suppress the subsynchronous vibration. The finite-element model of the turbocharger with floating-ring bearings is numerically solved for the nonlinear time-transient response. Both compressor and turbine added unbalance are induced and the dynamic stability is computed. The turbocharger model with linearized floating-ring bearings is also solved for eigenvalues to predict the modes of instability. The linear analysis demonstrates that the forward whirling mode of the floating-ring at the compressor end also becomes unstable at the higher turbocharger speeds, in addition to the unstable forward conical and cylindrical modes. The numerical predictions are also compared to the former experimental results of a similar turbocharger. The results of the study show that the subsynchronous frequency amplitude of the dominant first mode is reduced when inducing either the compressor or the turbine unbalance at a certain level.